2014
DOI: 10.1097/wnr.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Early print-tuned ERP response with minimal involvement of linguistic processing in Japanese Hiragana strings

Abstract: The act of reading leads to the development of specific neural responses for print, the most frequently reported of which is the left occipitotemporal N170 component of event-related potentials. However, it remains unclear whether this electrophysiological response solely involves print-tuned neural activities. The present study examined an early print-tuned event-related potential response with minimal involvement of linguistic processing in a nonalphabetic language. Japanese Hiragana words, nonwords, and alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 15 publications
4
23
2
1
Order By: Relevance
“…In contrast to our previous study with the same conditions except for task-relevancy (Okumura et al, 2014), the present study found a left-lateralized print-tuned response at 130-170 ms post-stimulus when the constituent characters were closely spaced. Moreover, unexpectedly, we found an enhanced early occipital ERP for words before 100 ms post-stimulus.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In contrast to our previous study with the same conditions except for task-relevancy (Okumura et al, 2014), the present study found a left-lateralized print-tuned response at 130-170 ms post-stimulus when the constituent characters were closely spaced. Moreover, unexpectedly, we found an enhanced early occipital ERP for words before 100 ms post-stimulus.…”
Section: Discussioncontrasting
confidence: 84%
“…Although an effect of spacing on leftlateralized N170 has not been studied previously, the print-tuned N1 in our former study was insensitive to this manipulation (Okumura et al, 2014). However, spacing has been shown to influence visual word processing and the neural activities of the VWFA (e.g., Cohen et al, 2008;Risko et al, 2011), a possible neural generator of the print-tuned N170 (e.g., Brem et al, 2006Brem et al, , 2009.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations